Manual of infection prevention and control - Damani, N. N. (Nizam N.); Damani, N. N. (Nizam N.). (Oxford : Oxford University Press, 2012)
This book provides clear, up-to-date and practical guidance on infection control in an easy to read format which can act as a quick source of reference on all aspects of healthcare-associated infections (HCAIs) for healthcare workers who are either directly or indirectly involved in prevention and control of HCAIs.
Previous ed.: published as Manual of infection control procedures. Cambridge: Cambridge University Press, 2006.
Description based on print version record.
Keywords: Nosocomial infections -- Prevention -- Handbooks, manuals, etc; Cross infection -- Prevention -- Handbooks, manuals, etc; Hospital buildings -- Disinfection -- Handbooks, manuals, etc